Learning the Zapin Bengkalis Dance Using the Nine Instructional Events Method in Grade XI at SMAN 3 Siak Hulu, Academic Year 2025/2026 - Nurul Hasanah; Nike Suryani (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
Learning is an interaction process between students, educators, and various learning resources within a planned environment (Suardi, Moh, 2018). Learning is understood as assistance provided by educators to students so that the process of acquiring knowledge, skills, attitudes, and values that support students’ personal development can occur. In this study, the researcher used a descriptive qualitative research method to obtain complete information from the research results by observing, collecting information, and describing the findings. The location of this research was SMAN 3 Siak Hulu. Based on these findings, it can be concluded that the stage of enhancing retention and transfer of learning plays an important role in learning the Zapin Bengkalis dance. For active students, this stage strengthens skill mastery and enables the application of the material in other contexts. Meanwhile, for passive students, this stage helps reinforce memory and increase confidence in dancing. The Nine Instructional Events method proposed by Robert Gagné is effective in teaching the Zapin Bengkalis dance because it can accommodate differences in student characteristics, both active and passive learners, and encourages more optimal student engagement in the learning process.